THE DEVELOPMENT OF LOGISTICS SCIENCE IN RUSSIA - B. Anikin; O. Anikin; I. Ermakov; S. Kuzminykh (Вестник университета)
The formation and development of logistics science in Russia has been shown as well as the place occupied in this process by the State University of Management and the Department of Logistics has been revealed. The structure of the scientific school of the Department of Logistics and its relationship with the domestic school of logistics have been shown. An attempt to comprehend critically the directions of development of logistics as a science has been made. The problems of the definition of logistics, discrepancies in the use of this term in scientific and practical activities have been adduced. Perspective directions of the development of modern logistics, developed by the Department of Logistics, have been shown. The system-forming trends in the development of supply chains, determining the further development of logistics as a science and field of activity, have been identified.